Penerapan Metode Resitasi untuk Meningkatkan Minat Belajar Siswa pada Materi Sejarah Pembaharuan Dunia Islam - Dudung Zenal Aripin (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2022)
This research was motivated by the low interest in learning SKI in class XII MIPA 3 students at MAN 1 Ciamis. The aims of the study were to: determine the initial steps of applying the recitation method to increasing student learning interest; know the process of applying the recitation method to increasing student learning interest; and know the success of applying the recitation method to increasing student learning interest. The method used is classroom action research, which consists of three cycles. The results showed that the teacher's ability to apply the recitation method in cycle I was 32, or 73%, in cycle II, 38, or 86%, and in cycle III, 42, or 95%. Students' interest in learning SKI increased from 60.87% in cycle 1 to 82.6% in the second cycle, reaching 91.3% in cycle 3. Students' test results increased from 76.30 in the pre-cycle to 78.70 in cycle 1, increased to 82.43 in cycle 2, and 87.43 in cycle 3. Student interest in learning SKI in groups obtained a score of 11.67, or 73%, in cycle I, increased to 13.5, or 84%, in cycle 2, and in cycle III, it became 14.67, or 92%, of the ideal score of 16. This proves that the recitation method can increase students' interest in learning the history of the renewal of the Islamic world (class XII MIPA 3 MAN 1 Ciamis).